Metodología para el diseño de una ciclo-infraestructura en una población urbana menor a 25.000 habitantes, caso particular municipio de Ubaté - Ruiz Fresneda, Esneyder Fernando (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
Currently, the purpose of the different urban settlements is to promote sustainable modes of transportation to improve the quality of life of the inhabitants. Colombian cities have begun to formulate programs and policies aimed at mitigating the effects of transportation and are configuring metropolitan areas whose purpose is to articulate the municipalities that are part of its conurbation. This situation affects municipalities that, although they are not in the metropolitan area, they are part of its boundaries. These municipalities become especially attractive for tourism in the region, i.e., they increase the number of visitors, especially on weekends and holidays. The effects associated with this situation translate, on the one hand, into economic growth and, on the other hand, into increased mobility. In addition, they have a direct impact on the behavior of the local population with respect to their travel and the use of the infrastructure available for this purpose. Therefore, the objective of this work is to generate a methodological design of a cycle infrastructure that can be implemented in a small municipality that has the characteristics described above and whose road network does not allow its expansion. The existing design manuals are designed for large urban settlements, so the objective is to identify a series of elements that are used in the manuals and can be implemented in a smaller municipality, but that meet technical requirements. The methodology is applied to the section of calle sexta between carrera once and carrera sexta in the municipality of Ubaté in Cundinamarca. Initially, information related to the norms that regulate mobility and behavior of urban design and planning that must be considered at the time of implementation, adaptation, and intervention in the infrastructure of the municipality is analyzed. For the methodological development, two surveys were conducted: the first one directly evaluates the mobility needs and the perception of the citizens regarding the current state of the roads and the use of bicycles as a means of transportation for short distances. The second survey is a gauging survey that shows the reasons for travel and the number of bicycles used in the area. The results of the proposed design indicate that the implementation of a bicycle infrastructure with the proper technical requirements contributes to increase the use of bicycles and can be used as a deterrent to the use of public space for on-street parking.
Keywords: Ciclo-infraestructura; Bicicletas; Movilidad sostenible; Señalización; Cycle Infrastructure; Urban Bikeway; Sustainable mobility; Road sign